Proposal for an Automated Form Finder System to Deduce the Authentic Morphology of Siirt Cas Houses - Berk, Mehmet Gokhan (SPRINGER INTERNATIONAL PUBLISHING AG, 2019)
This paper aims to summarize the steps taken towards the development of a semi-automated system in an attempt to create computer modeling of the original morphology of the individual buildings and respective urban texture for the so called cas houses which are the characteristic traditional buildings of the Siirt Province in Turkey. For the purpose of developing the proposed system, the architectural space forming methods that are closely related with the structural composition of the buildings where loose stones are joined with a strong and quick drying mortar are observed. It has been detected that cas houses are in fact built in time through an incremental expansion approach making use of repeating rectangular cells in horizontal plane coming side to side, and upper floor plans are developed almost identically to ground floor layout. The rhythmic layout of the facade elements such as doors and windows, cut rectangular pyramidal form of the buildings and specific elements such as stair covering vaults and underpasses are both enriching the building form and enabling easier detection of the original morphology of the buildings. The proposed form finding system is based on the principle of processing the approximately measured outer boundaries of the existing buildings to deduce internal spaces' sizes and layout which are in fact the sole sources causing the exterior building form for cas houses.
Keywords: Siirt cas houses; Heritage modeling; Automated plan generation; SHAPE GRAMMAR; GENERATION; Computer Science